Visual Tradisi Dalam Karya Seni Lukis Kontemporer Sebagai Wujud Artistik Pengaruh Sosial Budaya - Willy Himawan (Ornamen, 2013)
Visualization of tradition often appears in contemporaryworks in the form of signs or markers that link it to the visualizationof patterns in the tradition of works such as batik , wayangpainting , dance and so on. Due to the diversity of media andtype of artwork on the development of contemporary art , the dataprocessing of the contemporary works then leads to the readingof signs (visual) cultural given by the artwork , which is accompaniedby the development of accompanying cultural, the term ofcultural studies moved into visual culture (visual culture).The works are classified in several classes of work thattakes a visual tradition as a theme (context) , as follows ; 1. Thegroup 's work that simply displaying artifacts , visualization of traditionwithout making changes to the shape of the initial representation. 2. The Group's work that deforming the shape of the initialrepresentation visualization tradition.Research Focus On Artists Haryadi Suadi and I Wayan SudiartaIn Indonesia , the value of the tradition is not completelyexceeded (turned off) by modern values, but rather becomes acoexistent values. Research sharpened on the selection of twoartists whose each represent 2 classes of work in order to providea comprehensive assumptions initial review of the case ofthe emergence visualization of tradition in the works of contemporaryart as a socio-cultural artistic discourse. In the group withno change, selected artist I Wayan Sudiarta, Sudiarta did makechanges in his works that are visually different from the worksof Balinese traditional painting and derivatives. But however, it'sproviding a strong trace of visual on the composition of traditionpaintings like dancers and wayang tradition painting.In the change of tradition's group, selected artists HaryadiSuadi, because his works show changes almost in opposite directionswith Sudiarta, so that such elements are produced to bevery free, but still reminiscent of the elements of such a tradition .(Keywords : visual studies, visual deformation traditio , artcontext)Â